Pengaruh Kompetensi Auditor Internal dan Keadilan Organisasional Terhadap Pencegahan Fraud - Sitti Marwa Kharie; Ilfan Bereki (Peneliti.net, 2020)
This research aimed to known the effect of internal auditor competence and the justice organization toward prevention of fraud. The population of this research is Government Internal Controlling (APIP) in Inspektorat of North Moluccas. The method of taken sample is used multistage sampling. The technique which used to examine the hypotesa is simple regression.The result of this research is to show that internal auditor competence affect to prevention fraud justice organization is not affect to prevention fraud.